2009
DOI: 10.7210/jrsj.27.575
|View full text |Cite
|
Sign up to set email alerts
|

Ornithoid Gait Generation Based on Parametric Excitation

Abstract: We have applied a parametric excitation method to a kneed biped robot with semicircular feet and have shown that the robot can walk sustainably with only knee torque. A swing-leg of the kneed biped robot has similar mechanism to an acrobot, and many acrobots are controlled in inverse direction like ornithoid walking. These suggest that inverse bending of a knee restores more mechanical energy than forward bending, and hence, the ornithoid walking can be more efficient. In this paper, we first compare the forwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…To grow in efficiency, we think that optimization of the physical parameters of the biped robot is needed, for example mass and link length. Another method to grow in efficiency is the parametric excitation based inverse bending walking proposed by Harata et al [9], [10]. We will apply the proposed method to inverse bending walking and then gait become more efficiency.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To grow in efficiency, we think that optimization of the physical parameters of the biped robot is needed, for example mass and link length. Another method to grow in efficiency is the parametric excitation based inverse bending walking proposed by Harata et al [9], [10]. We will apply the proposed method to inverse bending walking and then gait become more efficiency.…”
Section: Discussionmentioning
confidence: 97%
“…Harata et al [6], [7] applied the parametric excitation method to a kneed biped robot, in which up-and-down movement of the center of mass was realized by bending and stretching knee, and showed that sustainable gait was generated by knee torque only. Harata et al [9], [10] also proposed parametric excitation based inverse bending walking in which the knee was bent in inverse direction to human.…”
Section: Introductionmentioning
confidence: 98%
“…There are 21 parameters, 2,4,5) and the maximum bending angle A m , in the definition of h. We impose 14 constraints, 8 of which are that the first and second derivatives at t = t 1 , t 3 , t 4 , t 6 equal zero, and the remaining six are that the first to third derivatives at points t 2 , t 5 are continuous. .…”
Section: Reference Trajectory Using Quartic Spline Curvementioning
confidence: 99%
“…A children's swing is an example using parametric excitation principle. Harata et al 4,5 also proposed parametric excitation-based inverse bending walking in which a swingleg knee was bent in the inverse direction to human. Harata et al 2,3 applied the parametric excitation method to a kneed biped robot, in which the up-and-down motion of the CoM was realized by bending and stretching a knee, and showed that sustainable gait was generated by knee torque only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation